Metafora Konseptual Leksikon Buah Pepatah-Petitih dalam Pepatah-Petitih Minangkabau - Nurul Khairumi (Balai Bahasa Provinsi Riau, 2024)
The research aims to analyze the conceptual metaphors within the fruit lexicons found in Minangkabau proverbs and identify the cultural values of the Minangkabau community through the proverbs. This study uses the qualitative descriptive method and the specific element sorting technique as the data collection method. The data used in this study were obtained from the book of proverbs written by H. Idrus Hakimy Dt. Rajo Penghulu and analyzed using the conceptual metaphor theory developed by Lakoff and Johnson, along with Kovecses’s approach. The results indicate that the conceptualization of fruits in Minangkabau proverbs reflects the relationships between humans and other humans, as well as between humans and God. The cultural values reflected in the proverbs include diversity, community life, and a sense of dependence on God. The fruit lexicon involved in this conceptual metaphor analysis includes durian, jackfruit (cubadak), mengkudu (mingkudu), and coconut (mumbang, kalapo, and karambia).